E‐NTPDase1/CD39 modulates renin release from heart mast cells during ischemia/reperfusion: a novel cardioprotective role. Issue 1 (15th October 2014) - Aldi, Silvia; Marino, Alice; Tomita, Kengo; Corti, Federico; Anand, Ranjini; Olson, Kim E.; Marcus, Aaron J.; Levi, Roberto
Abstract : Ischemia/reperfusion (I/R) elicits renin release from cardiac mast cells (MC), thus activating a local renin‐angiotensin system (RAS), culminating in ventricular fibrillation. We hypothesized that in I/R, neurogenic ATP could degranulate juxtaposed MC and that ecto‐nucleoside triphosphate diphosphohydrolase 1/CD39 (CD39) on MC membrane could modulate ATP‐induced renin release. We report that pharmacological inhibition of CD39 in a cultured human mastocytoma cell line (HMC‐1) and murine bone marrow‐derived MC with ARL67156 (100 mM) increased ATP‐induced renin release (≥2‐fold), whereas purinergic P2X7 receptors (P2X7 R) blockade with A740003 (3 mM) prevented it. Likewise, CD39 RNA silencing in HMC‐1 increased ATP‐induced renin release (≥2‐fold), whereas CD39 overexpression prevented it. Acetaldehyde, an I/R product (300 μM), elicited an 80% increase in ATP release from HMC‐1, in turn, causing an autocrine 20% increase in renin release. This effect was inhibited or potentiated when CD39 was overexpressed or silenced, respectively. Moreover, P2X7 R silencing prevented ATP‐ and acetaldehyde‐induced renin release. I/R‐induced RAS activation in ex vivo murine hearts, characterized by renin and norepinephrine overflow and ventricular fibrillation, was potentiated ( 2‐fold) by CD39 inhibition, an effect prevented by P2X7 R blockade. Our data indicate that by regulating ATP availability at the MC surface, CD39 modulates local renin release and thus, RAS activation, ultimately exerting a cardioprotective effect.—Aldi, S., Marino, A., Tomita, K., Corti, F., Anand, R., Olson, K. E., Marcus, A. J., Levi, R., E‐NTPDase1/ CD39 modulates renin release from heart mast cells during ischemia/reperfusion: a novel cardioprotective role. FASEB J. 29, 61–69 (2015). www.fasebj.org